(untitled) (Economic and Political Thought, 2012)
The article is aimed at demonstrating financial instruments used in foreign trade transactions, including especially those that let an importer be credited by an exporter, and also at assessing them from the point of view of an exporter. The author also tries to justify the role of logistics not only at the stage of a transaction implementation but also at the stage of negotiating the contract details, including payment issues. Firstly, she discusses financial instruments that are most frequently used in foreign trade transactions. These are also assessed against a criterion of payment certainty and the protection of the importer’s interests. Next, the author points out the essential logistic conditions for selected ways of payment and she analyzes issues of risk management in export transactions, especially types of risk connected with financing a transaction, crediting an importer or guaranteeing payment. The publication also contains a synthetic analysis of conditions for export financing strategies on two selected European markets.